Synthesis process and application of bio-based degradable polyester resin
Through the application of modified carbon fibers and composite fillers, the mechanical properties and degradation properties of bio-based polyester resins are improved, the problem of insufficient degradation performance in the prior art is solved, and better environmental friendliness is achieved.
Patent Information
- Application Number
- CN202510300679.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-14
AI Technical Summary
The degradation performance of existing bio-based hydroxy or carboxy polyester resins during use is insufficient, resulting in environmental pollution.
Through the use of modified carbon fiber and composite fillers, the interface compatibility between carbon fiber and polyester resin is improved, and the degradation of polyester resin is accelerated through the photodegradation mechanism.
It improves the tensile strength, bending strength and impact resistance of polyester resin, while accelerating its degradation process and reducing environmental pollution.
Smart Images

Figure CN119798940A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester resins, in particular to a synthesis process of a bio-based degradable polyester resin and application thereof. Background Art
[0002] The Chinese patent with publication number CN106715525B discloses a bio-based hydroxyl or carboxyl polyester resin characterized in that it is made from the following: a) an acid component, which includes: a1) at least one C4-C6 polycarboxylic acid or polycarboxylic anhydride, a2) at least one C8-C54 polycarboxylic acid or polycarboxylic anhydride, a3) optionally at least one C2-C22 saturated monoacid, b) an alcohol component, which includes: b1) at least one bio-based polyol with a functionality of at least 2, and at least one of the following two polyols b2) or b3): b2) at least one polyol with a functionality of at least 2 different from b1), b3) at least one polyol with a functionality of at least 3 different from b1) and b2). The resin is more particularly 100% bio-based. The invention also relates to a resin solution and a coating composition comprising the resin and its use in a coating having high strength and made from renewable raw materials. However, the degradation performance of the polyester resin prepared by the above-mentioned prior art during use needs to be improved; to this end, the present invention provides a bio-based degradable polyester resin synthesis process and its application to solve the above-mentioned problem. Summary of the invention
[0003] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a bio-based degradable polyester resin synthesis process and application thereof, which solves the problem of poor degradation performance of the above-mentioned polyurethane resin.
[0004] (II) Technical solution To achieve the above objectives, the present invention is implemented by the following technical scheme: A bio-based degradable polyester resin synthesis process, comprising the following synthesis steps: Step 1: Mix 1.4-2g of succinic acid and 1-1.6g of propylene glycol, add 0.12-0.2g of catalyst and 0.12-0.18g of inhibitor in sequence, raise the temperature to 145-160°C under nitrogen atmosphere, and react for 1.5-2h; Step 2: Evacuate to a vacuum degree of 0.07-0.09 MPa and continue the reaction at a temperature of 140-160°C for 4.5-5 hours; Step 3: Place in 12.5-20g of deionized water, cool to 80-90°C, stir for 25-35min, let stand, pour out the supernatant, evacuate to a vacuum degree of 0.07-0.09MPa, heat to 110-125°C, react for 2.5-3h, and then cool to room temperature; Step 4: Pour in 1.5-2g of diluent, stir evenly, then add 0.1-0.25g of initiator and 0.02-0.04g of accelerator, stir evenly; Step 5: Add 2.2-2.8 g of modified carbon fiber and 0.4-0.8 g of composite filler and mix well to synthesize bio-based degradable polyester resin.
[0005] Preferably, in step 1, the catalyst is tetrabutyl titanate and the inhibitor is hydroquinone.
[0006] Preferably, in step 4, the diluent is dimethyl itaconate, the initiator is cyclohexanone peroxide, and the promoter is cobalt cyclohexaneate.
[0007] Preferably, the preparation method of the modified carbon fiber is: (1) Soak 8-15 g of carbon fiber in 25-45 mL of the mixed solution; (2) Place in a 460-500W UV reactor and react for 30-40 minutes; (3) Wash with chloroform 2-4 times, and then dry in a drying oven at 50-60°C for 45-60 minutes to obtain modified carbon fiber.
[0008] Preferably, in (1), the mixed solution is a mixed solution of a mercapto polymer, chloroform and a,a-dimethoxy-a-acetophenone, and the volume ratio thereof is (0.2-0.6):0.5:(0.8-2).
[0009] Preferably, the preparation method of the thiol polymer is: 1-3g of bismaleimide, 0.8-2g of trimethylolpropane tris(3-mercaptopropionate) and 0.9-3g of triethylamine are mixed, 15-25mL of dichloromethane is added, the mixture is stirred and heated to 45-60°C, and reacted under a nitrogen atmosphere for 3.5-4h to obtain the thiol polymer.
[0010] Preferably, the preparation method of the composite filler is: S1. Mix 30-36 mL of isopropanol and 10-20 mL of N,N-dimethylformamide and stir for 10-20 min; S2, add 0.4-0.9g of tetrabutyl titanate, continue mixing and stirring for 10-15min, pour the mixture into a sealed container, heat to 200-220°C, and react for 20-24h; S3, take out and cool to room temperature, wash with anhydrous ethanol 3-5 times, centrifuge at a speed of 2500-3500r / mi for 8-10min, and then wash with deionized water 3-5 times; S4, first place it in a blast oven at 55-60°C and dry it for 10-12h, then place it in a muffle furnace, heat it to 420-450°C, and calcine it for 2h; S5, pour in 65-80mL of 4g / L H 2 PtCl 6 6H 2 0 solution, stirred for 22-24 hours, and then irradiated under a xenon lamp; S6. After centrifugation at a speed of 5000-7000 r / min for 10-13 min, wash with deionized water 2-4 times, and then dry in a drying oven at 50-60° C. for 22-24 h to obtain a composite filler.
[0011] Preferably, in S4, the heating rate is 5-7°C / min.
[0012] Preferably, in S5, the xenon lamp is equipped with a 400-420nm filter, the irradiation intensity is 280-300W, and the irradiation time is 50-60min.
[0013] Application of bio-based degradable polyester resin in packaging materials.
[0014] (III) Beneficial effects The present invention provides a bio-based degradable polyester resin synthesis process and its application. Compared with the prior art, it has the following beneficial effects: (1) The synthesis process and application of the bio-based degradable polyester resin comprises the following steps: modifying the carbon fiber so that a thiol polymer forms a coating on the surface of the carbon fiber, thereby improving the interfacial compatibility between the carbon fiber and the polyester resin and making the carbon fiber and the resin matrix more tightly bonded; the modification can reduce the mutual attraction between the carbon fibers, making them evenly dispersed in the resin matrix, preventing the agglomeration of the carbon fibers, thereby making the performance of the composite material more uniform, and improving the tensile strength, bending strength and impact resistance of the resin; and the thiol polymer coating and the degradation process of the polyester resin produce a synergistic effect, guiding or promoting the degradation of the polyester resin, so that the bio-based polyester resin can be better biodegraded after being discarded, thereby reducing pollution to the environment.
[0015] (2) The synthesis process of the bio-based degradable polyester resin and its application, through the composite filler absorbing light energy and generating free radicals, triggering the breakage of the polyester resin molecular chain, accelerating the photodegradation process, and facilitating the decomposition of the polyester resin in the natural environment, reducing white pollution; at the same time, the addition of the composite filler can change the surface properties of the polyester resin, making it easier for microorganisms to attach and decompose, thereby improving the degradation performance of the polyester resin; and the composite filler interacts with the polyester resin molecular chain to form chemical bonds or physical cross-linking points, thereby enhancing the bonding force between the molecular chains, thereby improving the mechanical properties of the polyester resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The SEM images of the carbon fibers provided by the present invention before and after modification; Figure 2 This is a comparison chart of the degradation performance test of the bio-based degradable polyester resin provided by the present invention. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In the present application, the carbon fiber is polyacrylonitrile-based carbon fiber purchased from Chengdu Luchen New Material Technology Co., Ltd.
[0019] Example 1
[0020] A bio-based degradable polyester resin synthesis process comprises the following synthesis steps: Step 1: Mix 1.4 g of succinic acid and 1 g of propylene glycol, add 0.12 g of tetrabutyl titanate and 0.12 g of hydroquinone in sequence, raise the temperature to 145° C. under a nitrogen atmosphere, and react for 1.5 h; Step 2: Evacuate to a vacuum degree of 0.07 MPa and continue the reaction at a temperature of 140°C for 4.5 hours; Step 3: Place in 12.5 g of deionized water, cool to 80°C, stir for 25 min, let stand, pour out the supernatant, evacuate to a vacuum degree of 0.07 MPa, heat to 110°C, react for 2.5 h, and then cool to room temperature; Step 4: Pour 1.5 g of dimethyl itaconate, stir evenly, then add 0.1 g of cyclohexanone peroxide and 0.02 g of cobalt naphthenate, and stir evenly; Step 5: adding 2.2 g of modified carbon fiber and 0.4 g of composite filler, and mixing well to synthesize bio-based degradable polyester resin; Wherein, the preparation method of modified carbon fiber: (1) After mixing 1 g of bismaleimide, 0.8 g of trimethylolpropane tris(3-mercaptopropionate) and 0.9 g of triethylamine, 15 mL of dichloromethane was added, the mixture was stirred and heated to 45°C, and reacted for 3.5 h under a nitrogen atmosphere to obtain a mercapto polymer; (2) 8 g of carbon fiber was immersed in 25 mL of a mixed solution of mercapto polymer, chloroform and a,a-dimethoxy-a-acetophenone in a volume ratio of 0.2:0.5:0.8; placed in a 460 W ultraviolet reactor and reacted for 30 min; washed twice with chloroform, and then dried in a drying oven at 50 ° C for 45 min to obtain modified carbon fiber; The preparation method of the composite filler is as follows: 30 mL of isopropanol and 10 mL of N, N-dimethylformamide are mixed and stirred for 10 minutes; 0.4 g of tetrabutyl titanate is added, and the mixture is poured into a sealed container, heated to 200°C, and reacted for 20 hours; taken out and cooled to room temperature, washed with anhydrous ethanol for 3 times, centrifuged at a speed of 2500r / mi for 8 minutes, and then washed with deionized water for 3 times; first placed in a blast oven at 55°C for 10 minutes, and then placed in a muffle furnace, heated to 420°C at a heating rate of 5°C / min, and calcined for 2 hours; 65 mL of H2O2 with a concentration of 4 g / L is poured in. 2 PtCl 6 6H 2 0 solution, stirred for reaction for 22 hours, and then irradiated under a xenon lamp equipped with a 400nm filter, with an irradiation intensity of 280W and an irradiation time of 50 minutes; centrifuged at a speed of 5000r / min for 10 minutes, washed twice with deionized water, and then dried in a drying oven at 50°C for 22 hours to obtain a composite filler.
[0021] Example 2
[0022] A bio-based degradable polyester resin synthesis process comprises the following synthesis steps: Step 1: Mix 1.7 g of succinic acid and 1.3 g of propylene glycol, add 0.16 g of tetrabutyl titanate and 0.15 g of hydroquinone in sequence, raise the temperature to 150° C. under a nitrogen atmosphere, and react for 1.8 h; Step 2: Evacuate to a vacuum degree of 0.08 MPa and continue the reaction at a temperature of 150° C. for 4.8 hours; Step 3: Place in 17.5 g of deionized water, cool to 85°C, stir for 30 min, let stand, pour out the supernatant, evacuate to a vacuum degree of 0.08 MPa, heat to 115°C, react for 2.8 h, and then cool to room temperature; Step 4: Pour 1.7 g of dimethyl itaconate, stir evenly, then add 0.2 g of cyclohexanone peroxide and 0.03 g of cobalt naphthenate, and stir evenly; Step 5: adding 2.5 g of modified carbon fiber and 0.6 g of composite filler, and mixing well to synthesize bio-based degradable polyester resin; Wherein, the preparation method of modified carbon fiber: (1) After mixing 2 g of bismaleimide, 1.9 g of trimethylolpropane tris(3-mercaptopropionate) and 1.9 g of triethylamine, 20 mL of dichloromethane was added, the mixture was stirred and heated to 50°C, and reacted for 3.7 h under a nitrogen atmosphere to obtain a mercapto polymer; (2) Soak 12 g of carbon fiber in 35 mL of a mixed solution of a mercapto polymer, chloroform and a,a-dimethoxy-a-acetophenone in a volume ratio of 0.4:0.5:1.4; place it in a 480 W ultraviolet reactor and react for 35 min; wash it with chloroform three times, and then dry it in a drying oven at 55 ° C for 50 min to obtain modified carbon fiber; The preparation method of the composite filler is as follows: 33 mL of isopropanol and 15 mL of N, N-dimethylformamide are mixed and stirred for 15 minutes; 0.6 g of tetrabutyl titanate is added, and the mixture is mixed and stirred for 12 minutes, and then the mixture is poured into a sealed container, heated to 210°C, and reacted for 22 hours; taken out and cooled to room temperature, washed with anhydrous ethanol 4 times, centrifuged at a speed of 3000r / mi for 9 minutes, and then washed with deionized water 4 times; first placed in a blast oven at 58°C for 11 hours, and then placed in a muffle furnace, heated to 440°C at a heating rate of 6°C / min, and calcined for 2 hours; 70 mL of H2O with a concentration of 4 g / L is poured in; 2 PtCl 6 6H 2 0 solution, stirred for reaction for 23 hours, and then irradiated under a xenon lamp equipped with a 410nm filter, with an irradiation intensity of 290W and an irradiation time of 55 minutes; after centrifugation at a speed of 6000r / min for 12 minutes, washed with deionized water for 3 times, and then dried in a drying oven at 55°C for 23 hours to obtain a composite filler.
[0023] Example 3
[0024] A bio-based degradable polyester resin synthesis process comprises the following synthesis steps: Step 1: Mix 2 g of succinic acid and 1.6 g of propylene glycol, add 0.2 g of tetrabutyl titanate and 0.18 g of hydroquinone in sequence, raise the temperature to 160° C. under a nitrogen atmosphere, and react for 2 h; Step 2: Evacuate to a vacuum degree of 0.09 MPa and continue the reaction at a temperature of 160°C for 5 hours; Step 3: Place in 20g of deionized water, cool to 90°C, stir for 35min, let stand, pour out the supernatant, evacuate to a vacuum degree of 0.09MPa, heat to 125°C, react for 3h, and then cool to room temperature; Step 4: Pour 2 g of dimethyl itaconate, stir evenly, then add 0.25 g of cyclohexanone peroxide and 0.04 g of cobalt naphthenate, and stir evenly; Step 5: adding 2.8 g of modified carbon fiber and 0.8 g of composite filler, and mixing well to synthesize bio-based degradable polyester resin; Wherein, the preparation method of modified carbon fiber: (1) After mixing 3 g of bismaleimide, 2 g of trimethylolpropane tris(3-mercaptopropionate) and 3 g of triethylamine, 25 mL of dichloromethane was added, the mixture was stirred and heated to 60°C, and reacted for 4 h under a nitrogen atmosphere to obtain a mercapto polymer; (2) Soak 15 g of carbon fiber in 45 mL of a mixed solution of a mercapto polymer, chloroform and a,a-dimethoxy-a-acetophenone in a volume ratio of 0.6:0.5:2; place it in a 500 W ultraviolet reactor and react for 40 min; wash it with chloroform 4 times, and then dry it in a drying oven at 60 ° C for 60 min to obtain modified carbon fiber; The preparation method of the composite filler is as follows: 36 mL of isopropanol and 20 mL of N, N-dimethylformamide are mixed and stirred for 20 minutes; 0.9 g of tetrabutyl titanate is added, and the mixture is mixed and stirred for 15 minutes, and then the mixture is poured into a sealed container, heated to 220°C, and reacted for 24 hours; taken out and cooled to room temperature, washed with anhydrous ethanol for 5 times, centrifuged at a speed of 3500r / mi for 10 minutes, and then washed with deionized water for 5 times; first placed in a 60°C blast oven for drying for 12 hours, and then placed in a muffle furnace, heated to 450°C at a heating rate of 7°C / min, and calcined for 2 hours; 80 mL of H2O with a concentration of 4 g / L is poured in. 2 PtCl 6 6H 2 0 solution, stirred for reaction for 24 hours, and then irradiated under a xenon lamp equipped with a 420nm filter, with an irradiation intensity of 300W and an irradiation time of 60 minutes; after centrifugation at a speed of 7000r / min for 13 minutes, washed with deionized water for 4 times, and then dried in a drying oven at 60°C for 24 hours to obtain a composite filler.
[0025] Comparative Example 1 Compared with Example 1, the difference is that the modified carbon fiber in Example 1 is replaced by carbon fiber; the rest remains unchanged.
[0026] Comparative Example 2 Compared with Example 1, the difference is that the composite filler in Example 1 is not added; the rest remains unchanged.
[0027] Mechanical properties test: The test was carried out on a universal material testing machine according to ASTM D2344 standard, and the test temperature was 25°C.
[0028] Tensile properties: tested in accordance with GB / T3354-2014; the results are shown in Table 1.
[0029] Bending properties: tested in accordance with GB / T2567-2008; the results are shown in Table 1.
[0030]
[0031] Degradation performance test: The polyester resin is made into a film with a size of 30mm×30mm×0.5mm, covered with non-toxic plastic mesh and buried in the soil at a depth of 25cm underground. The degree of degradation is measured every 2 weeks. Figure 2 As shown, compared with Comparative Example 1-2, the weight loss rate of the sample prepared in Example 1-3 is nearly 10% at 30 weeks, and it has good degradation performance.
[0032] like Figure 1 As shown in the figure, the surface of the carbon fiber before modification is smooth and neat; the surface of the modified carbon fiber becomes rough, and there are narrow grooves parallel to the longitudinal direction of the fiber, so that the polymer particle layer is dispersed on the fiber surface and grooves through adsorption, providing more contact points during the matrix compaction process, which helps to increase the interaction between the matrix resin and the fiber. At the same time, the modified carbon fiber has a more densely stacked structure, thereby improving the mechanical properties of the carbon fiber.
[0033] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0034] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0035] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A bio-based degradable polyester resin synthesis process, characterized in that: The synthesis steps include: Step 1: Mix 1.4-2g of succinic acid and 1-1.6g of propylene glycol, add 0.12-0.2g of catalyst and 0.12-0.18g of inhibitor in sequence, raise the temperature to 145-160°C under nitrogen atmosphere, and react for 1.5-2h; Step 2: Evacuate to a vacuum degree of 0.07-0.09 MPa and continue the reaction at a temperature of 140-160°C for 4.5-5 hours; Step 3: Place in 12.5-20g of deionized water, cool to 80-90°C, stir for 25-35min, let stand, pour out the supernatant, evacuate to a vacuum degree of 0.07-0.09MPa, heat to 110-125°C, react for 2.5-3h, and then cool to room temperature; Step 4: Pour in 1.5-2g of diluent, stir evenly, then add 0.1-0.25g of initiator and 0.02-0.04g of accelerator, stir evenly; Step 5: adding 2.2-2.8 g of modified carbon fiber and 0.4-0.8 g of composite filler, and mixing well to synthesize bio-based degradable polyester resin; The preparation method of the modified carbon fiber: (1) Soak 8-15 g of carbon fiber in 25-45 mL of the mixed solution; (2) Place in a 460-500W UV reactor and react for 30-40 minutes; (3) Washing with chloroform 2-4 times, and then drying in a drying oven at 50-60°C for 45-60 minutes to obtain modified carbon fiber; In the above (1), the mixed solution is a mixed solution of mercapto polymer, chloroform and a,a-dimethoxy-a-acetophenone, and the volume ratio thereof is (0.2-0.6):0.5:(0.8-2).
2. The process for synthesizing a biodegradable polyester resin according to claim 1, characterized in that: In the step 1, the catalyst is tetrabutyl titanate and the inhibitor is hydroquinone.
3. The process for synthesizing a biodegradable polyester resin according to claim 1, characterized in that: In the step 4, the diluent is dimethyl itaconate, the initiator is cyclohexanone peroxide, and the accelerator is cobalt cyclohexaneate.
4. The process for synthesizing a bio-based degradable polyester resin according to claim 1, characterized in that: The preparation method of the thiol polymer is as follows: 1-3 g of bismaleimide, 0.8-2 g of trimethylolpropane tris(3-mercaptopropionate) and 0.9-3 g of triethylamine are mixed, 15-25 mL of dichloromethane is added, the mixture is stirred and heated to 45-60° C., and the mixture is reacted for 3.5-4 hours under a nitrogen atmosphere to obtain the thiol polymer.
5. The process for synthesizing a bio-based degradable polyester resin according to claim 1, characterized in that: The preparation method of the composite filler is: S1. Mix 30-36 mL of isopropanol and 10-20 mL of N,N-dimethylformamide and stir for 10-20 min; S2, add 0.4-0.9g of tetrabutyl titanate, continue mixing and stirring for 10-15min, pour the mixture into a sealed container, heat to 200-220°C, and react for 20-24h; S3, take out and cool to room temperature, wash with anhydrous ethanol 3-5 times, centrifuge at a speed of 2500-3500r / mi for 8-10min, and then wash with deionized water 3-5 times; S4, first place in a blast oven at 55-60°C to dry for 10-12h, then place in a muffle furnace, heat to 420-450°C, and calcine for 2h; S5, pour into 65-80mL of H2PtCl6·6H20 solution with a concentration of 4g / L, stir and react for 22-24h, and then place under a xenon lamp for irradiation; S6. After centrifugation at a speed of 5000-7000 r / min for 10-13 min, wash with deionized water 2-4 times, and then dry in a drying oven at 50-60° C. for 22-24 h to obtain a composite filler.
6. The process for synthesizing a bio-based degradable polyester resin according to claim 5, characterized in that: In the step S4, the heating rate is 5-7°C / min.
7. The process for synthesizing a bio-based degradable polyester resin according to claim 5, characterized in that: In S5, the xenon lamp is equipped with a 400-420nm filter, the irradiation intensity is 280-300W, and the irradiation time is 50-60min.
8. Use of the bio-based degradable polyester resin according to claim 1 in packaging materials.
Citation Information
Patent Citations
Bio-based hydroxyl or carboxyl polyester resins
CN106715525B
Synthesizing method of bimetallic photocatalyst with hollow self-doped structure and application
CN107570197A
Method for preparing carbon nanofiber-based polyester film
CN108587085A
Preparation method of hyperbranched polymer / carbon nano tube / carbon fiber cross-scale reinforcement based on thiol-ene click reaction
CN109575287A
Preparation method of platinum modified titanium dioxide nanowire filter membrane
CN109908857A